Prestorage High CO2 and 1-MCP Treatment Reduce Chilling Injury, Prolong Storability, and Maintain Sensory Qualities and Antioxidant Activities of “Madoka” Peach Fruit - Tilahun, Shimeles; Jeong, Min Jae; Choi, Han Ryul; Baek, Min Woo; Hong, Jin Sung; Jeong, Cheon Soon (Frontiers in Nutrition, 2022)
Cold storage is widely used to prolong the storability of peach fruit. However, prolonged storage at low temperatures results in chilling injury (CI) in some susceptible peach cultivars during or after cold storage. Prestorage high CO2 and 1-MCP treatments are among the methods reported to alleviate CI and maintain the firmness of peach fruit. Hence, this study investigated CI, ripening-related physicochemical parameters, sensory qualities, total phenolics and flavonoids, and antioxidant activities of ‘Madoka’ peach fruit to observe the effectiveness of prestorage treatment with high CO2 and 1-MCP during the storage at 0 and 5°C. Based on the CI index, control fruit were acceptable for marketing up to 20 and 16 d of storage at 0 and 5°C, respectively, while treated fruit could be marketable up to 28 d of storage. The results of firmness and firmness related parameters (pectin content and polygalacturonase activity) also revealed that both high CO2 and 1-MCP treatments were effective in delaying the ripening process of ‘Madoka’ peach, and the storage at 0°C showed better results than 5°C. However, based on overall sensory evaluation results, the treated and control fruit were acceptable for marketing up to 20 and 12 d of storage, respectively, in both storage conditions. After deciding fruit marketability based on the combined objective postharvest quality parameters and subjective sensory qualities, we analyzed the changes in total phenolics, flavonoids, and antioxidant activities at harvest, on the 12 and 20th d of cold storage. Storage of ‘Madoka’ peach at 0°C maintained total phenolics, flavonoids, and antioxidant activities, regardless of prestorage treatment with high CO2 and 1-MCP. In summary, storing ‘Madoka’ peach fruit at 0°C after treating it with 30% CO2 for 6 h or 0.5 µL L-1 1-MCP for 24 h reduces CI, prolongs storability, and maintains sensory quality and antioxidant properties.